PENGARUH PENGGUNAAN GADGET TERHADAP PERKEMBANGAN SOSIAL DAN MORAL ANAK USIA DINI DI TK MUSLIMAT NU 6 AL-FAQIH SUKOANYAR-MALANG - Nurhayati; Nurhayati, Siti (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
Current technological developments have a major influence on children's behavior. Moreover, there are many AI (Artificial Intelligence) features through gadgets. The purpose of the study was to determine the effect of gadgets on children's social and moral behavior. The research methodology used is quantitative, combining survey/instrument data, interviews, documentation. The results of the research and discussion that have been managed are 52.3% to 54.5% identifying the existence of excessive gadget usage time limits, so that the impact of social behavior appears to be a change in personality attitudes that like to be alone and the resulting thinking patterns show passive and aggressive attitudes. Aggressiveness is shown in children's emotional attitudes that cannot be controlled, in addition, language patterns follow the work of the brain's imagination that imitates the meaning of words that appear in animated videos on YouTube or online games. If the analysis in terms of children's moral abilities is found to be lazy and lack of self-awareness to worship or when studying. Consciously, parents should not allow it, in reality, parents easily give gadgets after children have done the tasks given. The conclusion of the study is that the use of gadgets is very important to apply rules of limitation regarding the time of use, there needs to be a firm attitude regarding the use of gadgets, and self-agreement by parents in limiting the use of gadgets in front of children. This is done to pay attention to the growth and development of early childhood and can be done consistently.